(untitled) (Web of Teachers: Inderscience Research, 2025)
Lesson planning is a central aspect of the educational process and constitutes a purposeful, systematic, and reflective activity. Its theoretical underpinnings are embedded in a variety of educational philosophies, learning theories, and pedagogical frameworks, which collectively provide teachers with the principles and guidelines essential for crafting lessons that foster meaningful learning experiences. At its core, designing effective lesson plans draws heavily on the philosophical foundations of education, including perennialism, essentialism, progressivism, and constructivism. Each philosophy prescribes specific roles for teachers and students and shapes the organization, delivery, and assessment of instruction. These philosophies inform how knowledge is structured within lessons, the types of learning activities prioritized, and the means by which learning is evaluated. For instance, a lesson rooted in essentialism might emphasize a core body of knowledge, while a lesson grounded in constructivism would focus more on student-centered discovery and collaboration.